Urinary and plasma donor-derived cell-free DNA for noninvasive monitoring of BK polyomavirus-associated nephropathy in kidney transplant recipients: a prospective cohort study - Luying Guo; Sulin Luo; Rongfang Shen; Pengpeng Yan; Meifang Wang; Tianlu Zhang; Junhao Lv; Guangjun Liu; Hongfeng Huang; Zhimin Chen; Huiping Wang; Wenhan Peng; et al. (Renal Failure)
Background BK polyomavirus-associated nephropathy (BKPyVAN) is a major cause of allograft injury and dysfunction in kidney transplant recipients. Current monitoring tools, including viremia and biopsy, have limitations in sensitivity, invasiveness, and timing.Objective To evaluate donor-derived cell-free DNA (dd-cfDNA) in urine and plasma as a dynamic, noninvasive biomarker for monitoring treatment response and predicting rejection risk in patients with biopsy-proven BKPyVAN.Methods In this prospective cohort study, 25 kidney transplant recipients with biopsy-proved BKPyVAN were enrolled and stratified into two cohorts: conventional immunosuppression reduction (CISR, n = 20) and early immunosuppression reduction (EISR, n = 5). A total of 224 urine and plasma samples were collected before biopsy and at 1, 2, 3, and 6 months post-biopsy. dd-cfDNA levels were quantified and correlated with histological features and clinical outcomes.Results Urinary dd-cfDNA levels significantly declined in the CISR cohort by month 2 (p < 0.01), preceding changes in creatinine and BKPyV reads. In the EISR cohort, urinary dd-cfDNA levels remained stable, suggesting early therapeutic response. Plasma dd-cfDNA effectively identified acute rejection, with elevations in two CISR patients. Histologic injury patterns, including edema and cast formation, correlated with urinary dd-cfDNA concentrations (r = 0.44–0.51, p < 0.05).Conclusion Combined urinary and plasma dd-cfDNA measurements are promising for noninvasive, dynamic surveillance of BKPyVAN and rejection risk in kidney transplant recipients. Larger, multicenter studies are warranted to define clinical thresholds and standardize integration into immunosuppression management.